2016
DOI: 10.1007/s11695-016-2308-8
|View full text |Cite
|
Sign up to set email alerts
|

Whey Protein Supplementation Enhances Body Fat and Weight Loss in Women Long After Bariatric Surgery: a Randomized Controlled Trial

Abstract: Whey protein supplementation promoted body weight and FM loss in women with long-term weight regain following RYGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Interestingly, prior studies demonstrated that whey protein supplementation has fat mass, reducing effects in overweight and obese humans [48,49]. Similarly, high fat-fed mice consuming whey proteins were protected from early life weight gain and displayed improved glucose tolerance [50], suggesting that whey protein consumption has an anti-adipogenic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, prior studies demonstrated that whey protein supplementation has fat mass, reducing effects in overweight and obese humans [48,49]. Similarly, high fat-fed mice consuming whey proteins were protected from early life weight gain and displayed improved glucose tolerance [50], suggesting that whey protein consumption has an anti-adipogenic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, a total of 45 trials have been performed to investigate the effect of acute and chronic milk protein supplementation on various parameters related to glucose control, including glucose, insulin, GLP‐1, and GIP, in healthy subjects, and in patients with T2DM, metabolic syndrome, or prediabetes . Ideally, a meta‐analysis should be performed to quantify the effects of milk proteins on these parameters; however, the heterogeneous nature of the trials does not permit us to perform such an analysis.…”
Section: Summarizing the Evidence Of The Effects Of Milk Proteins On mentioning
confidence: 99%
“…Most short‐term trials found that the acute ingestion of milk proteins, particularly whey, stimulates incretin hormone secretion, increases the insulin response, and reduces postprandial glucose levels in healthy subjects and patients with T2DM. To the best of our knowledge, only four long‐term trials have investigated the glycemic and insulinemic effects of chronic milk protein supplementation. Of these long‐term trials, only one enrolled patients with T2DM .…”
Section: Summarizing the Evidence Of The Effects Of Milk Proteins On mentioning
confidence: 99%
See 2 more Smart Citations